Understanding the impact of regulatory reforms in children's residential child care : findings from an evidence review - Carl Purcell; Martin Elliott; Cindy Corliss; Mary Baginsky; Rebecca Playle; Alyson Rees; Michael Robling (Scottish Journal of Residential Child Care)
Children’s residential care in the United Kingdom is regulated by separate agencies in the four home nations to which responsibility for this area of public policy is devolved. The development of these regulatory systems has followed a long sequence of inquiries and scandals that have exposed serious failings in the provision of care to some children and young people. This article reports the findings of an evidence review considering the impact of regulatory reforms as part of a wider research project comparing the development of different systems of regulation across England and Wales. We identify four key themes from this review that should be addressed in the design of regulatory systems and explored through further research. These include: (1) balancing the enforcement of minimum standards against support for service improvement; (2) improving worker autonomy and relationship building with children and young people; (3) addressing unresolved debates regarding minimum qualification and ongoing training requirements; and (4) a stronger focus on organisational cultures and leadership within children’s residential homes and care home groups.